APLIKASI PENCARIAN JASA PANGKAS RAMBUT DI BANDAR LAMPUNG MENGGUNAKAN ALGORITMA A-STAR BERBASIS ANDROID - Ardi Susanto; Sharfina Febbi Handayani (Jurnal Data Mining dan Sistem Informasi, 2022)
Along with the development of car technology for various purposes. Such as online motorcycle taxis, delivery of goods, delivery services and so on. This potential can be developed in other lines such as barbershop services. By using an android-based application designed with the A* Algorithm, it can help the community to find the nearest barbershop route. It can also help barbershops to promote barber shops. The system is designed using extreme programming and UML methods and is built using the JAVA, XML, PHP and MySQL database programming languages. Then the application is tested using the blackbox method so that the application can run optimally.